The molecular ontogeny of follicular lymphoma: gene mutations succeeding the BCL2 translocation define common precursor cells. (29th December 2021) - Haebe, Sarah; Keay, William; Alig, Stefan; Mohr, Anne‐Wiebe; Martin, Larissa K.; Heide, Michael; Secci, Ramona; Krebs, Stefan; Blum, Helmut; Moosmann, Andreas; Louissaint, Abner; Weinstock, David M.; et al.
Summary: Relapsed follicular lymphoma (FL) can arise from common progenitor cells (CPCs). Conceptually, CPC‐defining mutations are somatic alterations shared by the initial and relapsed tumours, mostly B‐cell leukaemia/lymphoma 2 ( BCL2 )/immunoglobulin heavy locus ( IGH ) translocations and other recurrent gene mutations. Through complementary approaches for highly sensitive mutation detection, we do not find CPC‐defining mutations in highly purified BCL2 / IGH ‐negative haematopoietic progenitor cells in clinical remission samples from three patients with relapsed FL. Instead, we find cells harbouring the same BCL2 / IGH translocation but lacking CREB binding protein ( CREBBP ), lysine methyltransferase 2D ( KMT2D ) and other recurrent gene mutations. Thus, (i) the BCL2 / IGH translocation can precede CPC‐defining mutations in human FL, and (ii) BCL2 / IGH ‐translocated cells can persist in clinical remission.